2010
DOI: 10.1080/09712119.2010.9707126
|View full text |Cite
|
Sign up to set email alerts
|

Technical, Allocative and Economic Efficiencies of Turkish Dairy Farms: An Application of Data Envelopment Analysis

Abstract: Giinden, C., $ahin, A., Miran, B. and Yildinm, I. 2010. Technical, allocative and economic efficiencies of Turkish dairy farms : An application of data envelopment analysis. J. Appl. Anim. Res., 37: 213-216.Efficiencies of farms were measured using data envolepment analysis (DEA) on 87 dairy farms in hmir, Turkey. Technical, allocative and economic efficiencies were 0.615, 0.673 and 0.488, respectively. Only three farms were eficient. 62% of farms had decreasing return to scale. It is concluded that the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…Nearly three quarter of farms (77.76%) had the increasing return to scale while the remaining 23.26% of farms had constant return to scale. The reported same ratios for dairy farms were 9.0 and 18.0% in Australia, (Hambrusch et al, 2006), 28.7 and 9.2% in Turkey (Günden et al, 2010), and 19.0 and 17.0% in New Zealand (Wei, 2014), respectively. The farms with constant return to scale had nearly two times higher gross production value per cow than the farms with increasing return to scale (US $ 2590 against US $ (Table 3).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Nearly three quarter of farms (77.76%) had the increasing return to scale while the remaining 23.26% of farms had constant return to scale. The reported same ratios for dairy farms were 9.0 and 18.0% in Australia, (Hambrusch et al, 2006), 28.7 and 9.2% in Turkey (Günden et al, 2010), and 19.0 and 17.0% in New Zealand (Wei, 2014), respectively. The farms with constant return to scale had nearly two times higher gross production value per cow than the farms with increasing return to scale (US $ 2590 against US $ (Table 3).…”
Section: Resultsmentioning
confidence: 69%
“…The overall technical efficiency (0.66) was lower than that of 0.89 and 0.79 calculated for dairy cattle farms in Swedish and USA respectively (Tauer, 1993;Hansson, 2007), but similar to the values (0.65) calculated for dairy cattle farms in Australia (Balcombe et al, 2006). On the other hand, as the overall technical efficiency calculated for dairy cattle farms in Turkey was similar to (0.62) (Günden et al, 2010) our findings, the reported same figure of 0.488 and 0.217 for East African Countries and Jordan, respectively, were fairly lower (Ayele and Beatrice, 2010;Aldeseit, 2013) than that of our calculations.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Similarly, efficiency analysis has been applied relatively little in Turkey. There have been some studies on efficiency in Turkish agriculture (Gunden et al 1998;Zaim & Cakmak 1998;Akturk 2000;Demirci 2001;Ozcelik et al 2006), but there has thus far been no study carried out by applying data envelopment analysis (DEA) to hazelnut farms. Therefore, the objectives of this paper were to calculate farm level efficiency measures and to evaluate the determinants of cost efficiency in hazelnut farms in the Black Sea Region, Turkey.…”
Section: Introductionmentioning
confidence: 99%